Pengembangan Media Mincester untuk Meningkatkan Prestasi Belajar Sistem Kontrol Listrik - Sunan Hamri (Jurnal Pendidikan Vokasi Raflesia, 2021)
The purpose of this research are: (1) to design the development of mincester media to increase the learning achievement of the system controlling electromagnetic; (2) to describe the effectiveness the use of mincester media to increase the learning achievement of the system controlling electromagnetic. The subjects of these research are the students at Politeknik Raflesia electrical engineering major. While the object this research is mincester media as a treaning media the system controlling electromagnetic. This research was conducted using the approach of Research and Developmen (Research and Development). Based on the analysis that was conducted in this research, so it can be taken conclusion that: (1) minceste rmedia as a learning media that can exlain working principles of the system controlling electromagnetic components which abstract become concrete and attract the students’ attention so that it can increase the achievement in students’ learning. (2) mincester media is developed. It’s alternative media that is very effective as a learning media of the system controlling electromagnetic to increase the learning for students at Politeknik Raflesia electrical engineering major. The improvement of this achievement is very significant by t-test results 0.00 significance level of less than 5%. The use of mincester media can increase learning motivation. The learning motivation of the students' after using this mincester media is higher than before using minceste rmedia.